Vibration properties of and power harvested by a system of electromagnetic vibration energy harvesters that have electrical dynamics. (15th September 2017) - Cooley, Christopher G.
Highlights: Governing equations are derived for an arbitrary number of energy harvesting subsystems. Electrical dynamics occur due to inductance and capacitance in each circuit. Vibration behavior is determined from the matrix operator properties of the eigenvalue problem. These devices have multiple resonances where energy can be harvested. Devices with multiple subsystems can simultaneously power multiple electrical loads. Abstract: This study investigates the vibration and dynamic response of a system of coupled electromagnetic vibration energy harvesting devices that each consist of a proof mass, elastic structure, electromagnetic generator, and energy harvesting circuit with inductance, resistance, and capacitance. The governing equations for the coupled electromechanical system are derived using Newtonian mechanics and Kirchhoff circuit laws for an arbitrary number of these subsystems. The equations are cast in matrix operator form to expose the device's vibration properties. The device's complex-valued eigenvalues and eigenvectors are related to physical characteristics of its vibration. Because the electrical circuit has dynamics, these devices have more natural frequencies than typical electromagnetic vibration energy harvesters that have purely resistive circuits. Closed-form expressions for the steady state dynamic response and average power harvested are derived for devices with a single subsystem. Example numerical results for single and double subsystem devices show that the natural frequencies and vibration modes obtained from the eigenvalue problem agree with the resonance locations and response amplitudes obtained independently from forced response calculations. This agreement demonstrates the usefulness of solving eigenvalue problems for these devices. The average power harvested by the device differs substantially at each resonance. Devices with multiple subsystems have multiple modes where large amounts of power are harvested.